Między prawem a siłą. Stan wyjątkowy i inne przypadki zawieszenia reguł demokratycznego konstytucjonalizmu - Młynarska-Sobaczewska, Anna (PRAWO i WIĘŹ, 2025)
The paper presents the institution of a state of emergency from the perspective of fundamental concepts: power, democracy and constitutionalism. A state of emergency, understood as the suspension of the rules of constitutional separation and checks on power and the mandatory rule of law, is usually subject to serious subjective, procedural and temporal restrictions. The paper puts forward the thesis that the assumptions about the normative potential of regulations aimed at subjecting states of emergency to legal restrictions are illusory. An analysis of the conditions of a state of emergency: the circumstances of its introduction, its duration, and the negligible influence of democratic or judicial control over actions aimed at its introduction, as well as examples of practice despite the absence of a proclaimed state of emergency, points to the truth of the thesis about the decision-making nature of such actions.